Spatial heterogeneity in glassy polystyrene detected by deuteron NMR relaxation - Böhmer, Roland; Döß, A.; Diezemann, G.; Hinze, G.; Sillescu, H. (Wiley-VCH, 1999)
Using deuteron NMR, the dynamics of supercooled polystyrene-d3 was investigated near the calorimetric glass transition. At these temperatures non-exponential spin lattice relaxation is found, indicating the presence of spatial heterogeneity. With increasing temperature, structural relaxation becomes fast enough to average efficiently over different spatial environments, leading to exponential magnetization decays. A qualitative comparison with toluene as a representative of a low molecular weight glass former is carried out. Indications are found that in polystyrene the observed averaging process is more effective at Tg than it is in toluene.
Keywords: 530